Fossilization transforms vertebrate hard tissue proteins into N-heterocyclic polymers. Issue 1 (December 2018) - Wiemann, Jasmina; Fabbri, Matteo; Yang, Tzu-Ruei; Stein, Koen; Sander, P.; Norell, Mark; Briggs, Derek
Abstract Vertebrate hard tissues consist of mineral crystallites within a proteinaceous scaffold that normally degrades post-mortem. Here we show, however, that decalcification of Mesozoic hard tissues preserved in oxidative settings releases brownish stained extracellular matrix, cells, blood vessels, and nerve projections. Raman Microspectroscopy shows that these fossil soft tissues are a product of diagenetic transformation to Advanced Glycoxidation and Lipoxidation End Products, a class of N-heterocyclic polymers generated via oxidative crosslinking of proteinaceous scaffolds. Hard tissues in reducing environments, in contrast, lack soft tissue preservation. Comparison of fossil soft tissues with modern and experimentally matured samples reveals how proteinaceous tissues undergo diagenesis and explains biases in their preservation in the rock record. This provides a target, focused on oxidative depositional environments, for finding cellular-to-subcellular soft tissue morphology in fossils and validates its use in phylogenetic and other evolutionary studies. Recent studies have reported preservation of proteinaceous soft tissues within dinosaur bones. Here, Wiemann et al. combine analyses of fossil vertebrate tissues and experimentally matured modern samples to elucidate the mechanism of soft tissue preservation and the environments that favor it.